RISKS OF WORK ENVIRONMENT FOR SOCIAL WORK SPECIALISTS - Vīksniņa, Ina; Vītoliņa, Kristīne; Priede, Līga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article discusses research about the risks of work environment of social work specialists.In order institution wants to provide high quality service, it is important that staff maintain their mental and physical health in the long term. Daily work is physically hard because is associated with the movement of clients, long working hours, psychological load, daily inadequate socio-economic assessment and all this affects employee’s safety and health.Social Care Department lecturers from P. Stradins Medical College of the University of Latvia have carried out the study about the risks of work environment for social work specialists in social care and social rehabilitation institutions in order to identify the more common risks of work environment.The aim of the study was to ascertain the views of social work specialists about the risks of work environment in order to identify common risks of work environment in institutions of social care and rehabilitation. In implementation of the study were involved students from the Social Care Department as well as several social care and social rehabilitation institutions in Latvia. In realization of the study were utilized a couple of research methods - analysis of literature, guidelines, laws and regulations, and quantitative research method with the research instrument – questionnaire. The results of the study suggest that there are several risks of the work environment but as the main ones, after the analysis of staffs’ opinion, are psychological and ergonomic.